(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
This article is devoted to the issue of the creation of polyphonic meaning through word games in French newspapers (Le Monde, Le Figaro, Libération, L’Express). The linguistic and pragmatic functions of gender word games (calembour, contrepèterie, mot-valise, antanaclasis, syllepse) are analyzed within the framework of the study. The role of word games in the media is studied on the basis of M.Bakhtin’s theory of polyphony, O.Ducron’s theory of argumentation and pragmatic studies of contemporary French media. The article presents more than 50 real examples of headlines, which are divided into thematic groups and presented in tabular form.